SYNTHESIS, CRYSTAL STRUCTURE AND ANTITUMOR ACTIVITY OF A Zn(II) COMPLEX WITH 1,2-PHENYLENEDIOXYDIACETIC ACID - XI-SHI TAI; JIE YIN; YUAN-YUAN LIU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
A novel Zn(II) complex, [Zn(L)(H2O)3]·2H2O, has been obtained by reaction of Zn(OAc)2·2H2O with 1,2-phenylenedioxydiacetic acid in CH3OH/H2O. It was characterized by elemental analysis, IR and X-ray single crystal diffraction analysis. The crystal of the title complex belongs to monoclinic, space group C2/c with a = 29.283(7) Å, b = 6.7305(15) Å, c = 17.243(3) Å, β = 109.25(3)º, V = 3208.4(12) Å3, Z = 8, Dc = 1.621 mg·m-3, μ = 1.590 mm-1, F(000) = 1576, and final R1 = 0.1284, ωR2 = 0.3895. X-ray analysis reveals that the Zn(II) center is seven-coordination with a O7 distorted pengonal bipyramidal coordination environment. The Zn(II) complex molecules form 1D chain structure by the hydrogen bonds and π-π stacking interactions. The antitumor activity of 1,2-phenylenedioxydiacetic acid ligand and its Zn(II) complex against human intestinal adenocarcinoma HCT-8 cells, lung adenocarcinoma HCT-116 cells and human lung adenocarcinoma A549 cells line have been investigated.